Analysis of the Effect of Human Resource Planning, Quality of Work Life and Compensation on Employee Work Performance at PT. Supermarkets Maju Bersama Medan - Sahat Simbolon; Agus Susanto; Rico Nur Ilham (Universitas Dharma Wacana, 2022)
This study aims to describe the effect of human resource planning, quality of work life and compensation on employee performance at PT. Supermarkets Forward Together with Medan. This research was conducted for 3 (three) months, starting from March 2022 to May 2022. This study used the proportional random sampling method. The respondents of this study were all cashiers at PT. The Maju Bersama Supermarket in Medan with a total of 120 (one hundred and twenty) employees. The research instrument is a questionnaire to collect data from human resource planning variables, quality of work life variables, compensation variables and employee performance variables. Data analysis techniques used are validity test, reliability test, descriptive analysis, multicollinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test t test, simultaneous hypothesis test or F test, and calculation of the coefficient of determination. The results of descriptive analysis for human resource planning variables are in the good category, for the quality of work life and compensation variables are in the fairly good category, and for the employee performance variable in the good category, at PT. Supermarkets Forward Together with Medan. Based on the partial analysis, human resource planning, quality of work life and compensation have a positive and significant effect on employee performance at PT. Supermarkets Forward Together with Medan. Simultaneously human resource planning, quality of work life and compensation have a positive and significant effect on employee performance at PT. Supermarkets Forward Together with Medan. The contribution of human resource planning variables, quality of work life and compensation to the increase in employee performance variables is 0.737 or 73.7%, while the remaining 0.263 or 26.3% is influenced by other variables not examined in this study, such as work. ethics, competence, leadership and others. like work. ethics, competence, leadership and others. like work. ethics, competence, leadership and others.